Age-dependency of neurite outgrowth in postnatal mouse cochlear spiral ganglion explants - Mirretto Barone, Claudia; Fink, Stefan; Schmidbauer, Dominik; Rousset, Francis; Eickhoff, Holger; Tropitzsch, Anke; Kramer, Benedikt; Senn, Pascal; Glueckert, Rudolf; Rask-Andersen, Helge; Wiesmüller, Karl-Heinz; Löwenheim, Hubert; et al. (Brain Sciences, 2020)
Background: The spatial gap between cochlear implants (CIs) and the auditory nerve limits frequency selectivity as large populations of spiral ganglion neurons (SGNs) are electrically stimulated synchronously. To improve CI performance, a possible strategy is to promote neurite outgrowth toward the CI, thereby allowing a discrete stimulation of small SGN subpopulations. Brain-derived neurotrophic factor (BDNF) is effective to stimulate neurite outgrowth from SGNs. Method: TrkB (tropomyosin receptor kinase B) agonists, BDNF, and five known small-molecule BDNF mimetics were tested for their efficacy in stimulating neurite outgrowth in postnatal SGN explants. To modulate Trk receptor-mediated effects, TrkB and TrkC ligands were scavenged by an excess of recombinant receptor proteins. The pan-Trk inhibitor K252a was used to block Trk receptor actions. Results: THF (7,8,3′-trihydroxyflavone) partly reproduced the BDNF effect in postnatal day 7 (P7) mouse cochlear spiral ganglion explants (SGEs), but failed to show effectiveness in P4 SGEs. During the same postnatal period, spontaneous and BDNF-stimulated neurite outgrowth increased. The increased neurite outgrowth in P7 SGEs was not caused by the TrkB/TrkC ligands, BDNF and neurotrophin-3 (NT-3). Conclusions: The age-dependency of induction of neurite outgrowth in SGEs was very likely dependent on presently unidentified factors and/or molecular mechanisms which may also be decisive for the age-dependent efficacy of the small-molecule TrkB receptor agonist THF.